The Representation of Global Competence in a Senior High School English Textbook in Indonesia - Sharizan, Sharizan; Yulia, Yuyun; Handayani, Riris; Titania, Fani Nabila; Thamrin, Andi Hidayat (AL-ISHLAH: Jurnal Pendidikan, 2024)
Global competence (GC) helps to overcome multidimensional problems that should be learned in education. The integration of it can be done through the English for Change textbook which is the current and latest English textbook applying the Merdeka Curriculum. This research investigates the representation of GC in the English for Change textbook for 11th-grade Indonesian senior high school students. This qualitative research employed Critical Discourse Analysis (CDA) to evaluate and analyze the representation of GC in the 'English for Change’ textbook, which follows the Merdeka Curriculum. The analysis was started by reading and codifying some parts of the textbook to four dimensions of GC from OECD PISA, which are examining the local, global, and intercultural problems; understanding and appreciating various perspectives from others; engaging in open, appropriate, and effective multicultural interaction; and taking action for the development and sustainability of well-being. The finding reveals that GC is represented sufficiently which can be found in 59 pages in the book. The most dimension used is to take action for collective well-being and sustainable development with a percentage of 42.37%. However, examining local, international, and intercultural problem dimensions should be exposed more in the book with a percentage of only 11.86%. Therefore, teachers and students need to learn GC through the English for Change textbook and expand additional insights about multidimensional problems through other learning resources besides the English for Change textbook.